2022
DOI: 10.1371/journal.pone.0270921
|View full text |Cite
|
Sign up to set email alerts
|

Impact of frailty in elderly patients with moderate to severe asthma

Abstract: Frailty assessment has been identified as critical approach in chronic respiratory diseases with substantial impact in the health status and functionality in later life. Aging modifies the immune response leading to a chronic pro-inflammatory state and increased susceptibility to airway infections. Since epigenetic changes, airway epithelium dysfunction and inflammatory cytokine activity seem to be more pronounced in the immunosenescence, elderly asthmatics are at higher risk of poor clinical outcomes. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…In this study, a high prevalence of frailty and pre-frailty was observed among older adults Chinese patients with asthma, suggesting that routine frailty assessment could benefit the management of asthma in this population. Evidence also supports the role of frailty as a significant risk factor for the development and progression of asthma (12). These findings underscore the potential for a bidirectional causal association between asthma and frailty, emphasizing the need to clarify this relationship to inform prevention and treatment strategies for both conditions.…”
Section: Introductionmentioning
confidence: 63%
“…In this study, a high prevalence of frailty and pre-frailty was observed among older adults Chinese patients with asthma, suggesting that routine frailty assessment could benefit the management of asthma in this population. Evidence also supports the role of frailty as a significant risk factor for the development and progression of asthma (12). These findings underscore the potential for a bidirectional causal association between asthma and frailty, emphasizing the need to clarify this relationship to inform prevention and treatment strategies for both conditions.…”
Section: Introductionmentioning
confidence: 63%
“…The recognition of asthma in ageing is frequently delayed and the treatment postponed due to difficulties that clinicians have in the approach in older asthmatic patient. Recently, a study protocol on the role of frailty in older patients with diagnosis of moderate-to-severe asthma according to guidelines [ 17 ] has been published by a group of researchers from Brazil, which may help characterise this group of patients [ 32 ]. A greater number of future studies and a multidisciplinary management of asthma in older adults are still needed.…”
Section: Discussionmentioning
confidence: 99%
“…Age-related changes in HRQoL experiences are variable such that significant constitutional heterogeneity exists among older patients from very “fit” to very “frail”. 61 Overall, frailty in gross and fine motor skills can affect asthma severity in elderly patients who struggle with hand eye coordination deficits possibly leading to ineffective use of prescribed inhalers. Neurocognitive impairments and decreased memory can affect the elderly in regular medication adherence, especially in the setting of polypharmacy.…”
Section: Th P: Problems For Elderly Asthmatics (Barriers Not Otherwis...mentioning
confidence: 99%